2021
DOI: 10.20867/thm.27.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Convention Specific Dimensions on Universities Teaching Staff Behavioral Intention

Abstract: Purpose – The aim of this paper is to assess the influence of participation frequency at the conventions on universities teaching staff’s behavioral intentions. Design –The convention tourism attendees’ behavioral intentions evaluation was conducted through the constructs of site-specific dimensions and convention-specific dimensions. Methodology – In order to test proposed hypotheses, following establishment of measurement invariance across groups, structural equation model was fitted to both groups of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(26 citation statements)
references
References 0 publications
2
18
0
6
Order By: Relevance
“…Push factors are the intangible or psychological factors intrinsic to event participants that drive them to decide to attend a MICE event. Related studies have indicated the importance of networking and educational opportunities as push motivational factors (Cassar, Whitfield, Chapman, 2020;Dimitrovski, Seočanac, Luković, 2021;Gračan, Barkiđija Sotošek, Torbarina, 2021;Kim, Kim, Oh, 2020;Kim, Lee, Kim, 2012;Lee, Koo, Chung, 2019;Mair, Thompson, 2009;Pavluković, Cimbaljević, 2020;Severt et al, 2007;Yodsuwan, Pathan, Butcher, 2020;Yoo, Chon, 2008;Yoo, Zhao, 2010). The following sections explain these factors in detail.…”
Section: Push Factorsmentioning
confidence: 95%
See 3 more Smart Citations
“…Push factors are the intangible or psychological factors intrinsic to event participants that drive them to decide to attend a MICE event. Related studies have indicated the importance of networking and educational opportunities as push motivational factors (Cassar, Whitfield, Chapman, 2020;Dimitrovski, Seočanac, Luković, 2021;Gračan, Barkiđija Sotošek, Torbarina, 2021;Kim, Kim, Oh, 2020;Kim, Lee, Kim, 2012;Lee, Koo, Chung, 2019;Mair, Thompson, 2009;Pavluković, Cimbaljević, 2020;Severt et al, 2007;Yodsuwan, Pathan, Butcher, 2020;Yoo, Chon, 2008;Yoo, Zhao, 2010). The following sections explain these factors in detail.…”
Section: Push Factorsmentioning
confidence: 95%
“…Based on the extensive literature review, six motivational factors influencing tourists' decision to re-attend MICE events can be identified. From these, there are two push factors namely networking and educational opportunities (Cassar, Whitfield, Chapman, 2020;Dimitrovski, Seočanac, Lukovići, 2021;Gračan, Barkiđija Sotošek, Torbarina, 2021;Kim, Kim, Oh, 2020;Kim, Lee, Kim, 2012;Lee, Koo, Chung, 2019;Mair, Thompson, 2009;Pavluković, Cimbaljević, 2020;Severt et al, 2007;Yodsuwan, Pathan, Butcher, 2020;Yoo, Chon, 2008;Yoo, Zhao, 2010), and four pull factors namely destination image, travel cost, attractions and accessibility (Abulibdeh, Zaidan, 2017;Al-Dweik, 2020;Choi, 2013;Fitri, 2021;Gračan, Barkiđija Sotošek, Torbarina, 2021;Hashemi et al, 2020;Houdement, Santos, Serra, 2017;Kim, Kim, Oh, 2020;Lee, Koo, Chung, 2019;Mair, Thompson, 2009;Tanford, Montgomery, Nelson, 2012;Weru, Njoroge, 2021;Yoo, Chon, 2008). The next sections will discuss the influence of push and pull factors on tourists' decisions to re-attend MICE events in detail.…”
Section: Push and Pull Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the current trend of significant decrease of participants at individual conventions, understanding the evaluations of convention attendees becomes more important than ever (Gračan et al 2021). Business travelers are discerning guests with a high paying power.…”
Section: Exhibitionsmentioning
confidence: 99%